Chemical diversity and biological activity of endemic plants of Kuala Keniam, Taman Negara Pahang / Nor Hadiani Ismail … [et al.] - Ismail, Nor Hadiani; Ahmad, Rohaya; Ahmat, Norizan; Mohd Jaafar, Faridahanim (Research Management Institute (RMI), 2011)
Tropical plants with diverse chemical complexities are undoubtedly the most important natural resource in the search for bioactive natural products with potential use in pharmaceutical applications and healthcare. Seventy-six plant species of interest from twenty-five families were collected during two phytochemical expeditions in Kuala Keniam, Pahang. The plants were from family Rubiaceae, Annonaceae, Lecythidaceae, Myristicaceae, Tiliaceae, Rosaceae, Moraceae, Ulmaceae, Menispermaceae, Euphobiaceae, Lauraceae, Ebenaceae, Verbanaceae, Myrsinaceae, Simaroubaceae, Leeaceae, Rutaceae, Melastomaceae, Sterculiaceae, Celastraceae, Commelinaceae, Burseraceae, Convolvulaceae, Guttiferae and Pandanaceae. The plants were screened on site for presence of alkaloids and flavonoids. Several plants with high content of alkaloids and flavonoids were found. Alkaloids and flavonoids are classes of compounds with many therapeutic activities such as antioxidant, antimicrobial, anticancer and others. Selected plants were assayed for biological activities. 143 extracts produced from various parts of the plants were evaluated for free radical scavenging and anbacterial activities. As a results, 12 extracts were found to strong free radical scavengers, 9 extracts were moderate while others exhibited weak or no activity. For antibacterial screening, a dosage of 100 jug of each plant extract was subjected to disc diffusion antibacterial assay using 12 bacteria strains. Inhibition zones of 10 to 15 mm are regarded as moderate activity where as inhibition zones of more than 15 are considered strong. Inhibition zones of 7-10 mm are considered weak. Two plants from genus Knema, which are Knema Malayana and Knema glauca was found to possess promising antibacterial activity. For antidiabetic properties, 47 extracts were assayed for aamylase and oc-glucosidase inhibitory activities. Four plant species demonstrated potent aamylase inhibition. The plants were Burkillantus malaccensis (stem), Horsfieldia polysherula (leaves and stem) Labisia pumila (leaves and root) and Phyllanthus pulcher (stem). The IC50 values of these extracts ranged from 1.2 to 2.8 |ug ml"1. Four plant species may be classified as strong a-glucosidase inhibitors with IC50 values ranging from 2.4 to 6.1 \ig ml"1. The plants were Gironniera parvifolia (stem), Horsfieldia polyspherula (leaves and stem), Phyllanthus pulcher (leaves and stem) and Rothmannia schoemanii (stem). Extracts of P. pulcher (stem) and H. polyspherula (leaves and stem) showed potent inhibitory activity against both enzymes. These data suggest that these plant extracts are potentially useful in the development of new antidiabetic remedies. Detailed phytochemical studies on Renellia elliptica lead to the isolation of interesting molecules; 2-Formyl-3-hydroxy-9,10- anthroquinone and 1,3-Dihydroxy-2-methoxymethyl-9,10-anthraquinone which may become a platform for development of various useful commercial healthcare and pharmaceutical products form our tropical plants.